Factors discouraging HIV testing. - Frederick Nchang Cho (14485735) (2025)
Background Human Immunodeficiency Virus (HIV) remains a major public health concern in sub-Saharan Africa. In Cameroon, young people are disproportionately affected but underrepresented in HIV testing statistics. Objective To explore knowledge, attitudes, and behaviours related to HIV testing among youth in Kumba, Cameroon, and to identify barriers to inform community-based interventions. Methods A cross-sectional qualitative study was conducted using nine focus group discussions (FGDs) with 75 youth (52 females and 23 males) aged 18 - 35 years across four quarters in the Kumba II municipality. Participants were purposively sampled to reflect diverse educational and occupational backgrounds. Data were thematically analysed using Braun and Clarke’s framework with NVivo Version 14. Results Participants demonstrated high awareness of HIV testing services (90.7%) and transmission via sexual contact (96.0%), though knowledge gaps remained regarding non-sexual transmission and testing procedures. While 93.3% had previously undergone HIV testing, 57.3% reported stigma and 46.7% raised confidentiality concerns as ongoing barriers. Female participants feared being labelled as promiscuous, while males cited social norms that discourage help-seeking. Most participants supported school-based or youth-centred community testing, emphasising the need for privacy and youth-friendly environments. Key motivators for testing included the desire to know one’s status (82.7%), symptom appearance (28.0%), and unprotected sex (17.3%). Conclusions Despite strong awareness and high testing uptake, stigma and confidentiality concerns persist among youth in Kumba. To enhance HIV testing rates, community-based strategies should prioritise mobile clinics, peer outreach, and confidential youth-centred services. Strengthening education about HIV transmission and demystifying the testing process may further reduce barriers.